A Study to Assess the Effectiveness of Protocol on Care of Newborn in Phototherapy on Knowledge and Practice among Nurses at Selected Hospitals in South India (Indian Journal of Public Health Research & Development, 2020)
Background: The present study assess the Effectiveness of Protocol on Care of Newborn in Phototherapy on Knowledge and Practice among Nurses at Selected Hospitals in South India Method and Material: A pre - experimental one group pre and post test study design was used to collect all the necessary and relevant data from nurses. The study was conducted in the maternity ward and phototherapy unit of two hospitals. Based on inclusion criteria 50 nurses were selected and non probability convenient sampling techniques were used. Results: In pre test level of knowledge of nurses regarding care of newborn in phototherapy, 17 (34%) had inadequate knowledge, 19 (38%) had moderately adequate knowledge and 14 (28%) had adequate knowledge. In post test majority of 44(88%) had adequate knowledge, 6 (12%) had moderately adequate knowledge and no one had inadequate knowledge. The improved mean value for knowledge was 10.43 with “t” value of 13.47 and improved mean value for practice was 6.78 with “t” value of 17.26. This results shows the high statistical significance at p
Keywords: Protocol, Nurses, Newborn, Knowledge, Practice, Hospital and south India.